Perceptions of Scholars on the Internernet Censorship in Turkey: A Case of the Hacetttepe University Faculty of Letters - Eroğlu, Şahika; Yılmaz, Bülent (Information World, 2015)
The Internet that referred as the printing press of our age has turn into a berely controlled platform due to the advancements of access and sharing facilities. In this context, it’s also referred in the literature that restriction of access to the Internet is described as the Internet censorship and that affects every user. In the light of this information, as one of the intensive user groups of the Internet, scholars’ perceptions on the Internet censorship were evaluated and their opinions were analysed via a web-based survey. The survey delivered to 218 scholars at Hacettepe University Faculty of Letters by e-mail and it is generated 47 responses. The findings obtained in this study reflected that, scholars are the intensive users of the Internet and social media and social media for the purpose education and research. Based on these findings, restrictions on the Internet affected scholars in many dimensions. In the end of the study, the requirements on description of boundaries about restrictions that will provide distinction between harmful and useful content is highlighted.
Keywords: Censorship; Internet censorship; Intellectual freedom; Academics; Turkey